Projeto hidrodinâmico de turbina hidrocinética por meio de simulação numérica computacional e técnicas de otimização - Labigalini, Luan Cavalari (2021)
Small wind turbines (SWT) and hydrokinetic turbines (HT) are affordable ways to distribute power generation from renewable resources. In order to better harness such available sources and to design future equipment as efficient as possible, this work aims to develop a layout optimization. Firstly, the Blade Element Momentum (BEM) method is applied to validate the aerodynamic models from literature with experimental data. It intends to replicate turbine operation and its performance. The power and thrust curves could be wellpredicted according to tipspeed ratio (TSR) variation. Secondly, metaheuristic algorithms based on natural behaviour are used to find the best hydrokinetic turbine design in a hypothetical environment subjected to a single person's electricity demand. The optimization was carried out concerning power and blade inertia, and the layout parameters used as input were the rotor diameter, the number of blades, and the rotational speed. The turbine developed was simulated in a CFD manner, in order to validate torque result. Thirdly, a correction concerning drag and lift coefficient was conducted based on solidity effects between blades. It was built from parameters obtained at CFD simulations of an hydrofoil array. Finally, a protuberance was added into hydrofoil’s leading edge aiming a decrease of drag and an improvement of lift. Cavitation effect was taking into account and tried to be avoided at chord calculation. The most efficient algorithm could find a turbine with a power coefficient 18% lower than the Betz Limit. The solidity effect promoted 8,15% of difference in comparison with optimized power coefficient. The protuberance harmed lift and drag coefficient, and allowed cavitation effect. Its impact on blade inertia was a growth of 177,61%.